PENGARUH PENGGUNAAN LOGO HALAL NONRESMI, LITERASI HALAL, DAN KUALITAS INFORMASI TERHADAP KEPERCAYAAN KONSUMEN MUSLIM PADA PRODUK MAKANAN DI MARKETPLACE DIGITAL - Nurul Izzaty; Yan Putra Timur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing use of digital marketplaces as a platform for purchasing food products has made Muslim consumers increasingly dependent on the information provided by sellers to assess product quality and halal status. As the country with the largest Muslim population in the world, Indonesia places halal compliance as one of the primary considerations in food consumption decisions. In digital transactions, consumers cannot directly inspect products and therefore rely heavily on the information available on the platform. However, the continued use of unofficial halal logos, varying levels of halal literacy, and the inconsistent quality of product information may influence Muslim consumers’ trust in food products marketed through digital marketplaces. This study aims to analyze the effects of unofficial halal logo usage, halal literacy, and information quality on Muslim consumer trust in food products sold through digital marketplaces. This research employed a quantitative approach with a causal associative research design. Primary data were collected through questionnaires distributed to 100 Muslim consumers aged 17–30 years in East Java who had previously purchased food products through digital marketplaces. The sampling technique used was non-probability sampling, and the data were analyzed using multiple linear regression. The results indicate that the use of unofficial halal logos, halal literacy, and information quality each have a positive and significant effect on Muslim consumer trust. Information quality was found to be the most dominant variable influencing consumer trust. Furthermore, all three variables simultaneously have a significant effect on Muslim consumer trust in food products sold through digital marketplaces.